2017
DOI: 10.1371/journal.pone.0173911
|View full text |Cite
|
Sign up to set email alerts
|

Terpene synthases from Cannabis sativa

Abstract: Cannabis (Cannabis sativa) plants produce and accumulate a terpene-rich resin in glandular trichomes, which are abundant on the surface of the female inflorescence. Bouquets of different monoterpenes and sesquiterpenes are important components of cannabis resin as they define some of the unique organoleptic properties and may also influence medicinal qualities of different cannabis strains and varieties. Transcriptome analysis of trichomes of the cannabis hemp variety ‘Finola’ revealed sequences of all stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
208
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(224 citation statements)
references
References 49 publications
14
208
0
2
Order By: Relevance
“…To this end, a mapping experiment is in progress using a larger sample of Oregon Promise doubled haploids. That larger and more robust data set can be used, together with the available barley genome sequence (21) and metabolomic data, to identify candidate genes and biochemical pathways for specific flavors, as described for tomato and cannabis (8,37).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a mapping experiment is in progress using a larger sample of Oregon Promise doubled haploids. That larger and more robust data set can be used, together with the available barley genome sequence (21) and metabolomic data, to identify candidate genes and biochemical pathways for specific flavors, as described for tomato and cannabis (8,37).…”
Section: Discussionmentioning
confidence: 99%
“…Beta and alpha-Caryophyllene are the major sesquiterpenes encountered in the Cannabis plant [85]. Importantly, a comparative study showed that regardless the type of extraction used supercritical fluid extraction, steam distillation, or hydrodistillation, the major sesquiterpene compound to be extracted was β-Caryophyllene (BCP) [86].…”
Section: Beta (β)-And α-Caryophyllenementioning
confidence: 99%
“…β-elemene (1-methyl-1-vinyl-2,4-diisopropenyl-cyclohexane) is a derivative terpenoid found in Cannabis sativa, which may arise due to oxidation or due to thermal-or UV-induced rearrangements during processing or storage [85,178,179]. However, β-elemene is present not only in Cannabis sativa but also from Curcuma rhizome, and it is commonly used in traditional Chinese medicine due to its anticancer properties with no reported severe side effects [180].…”
Section: β-Elemenementioning
confidence: 99%
“…On the other hand, the tendency of man to improve and select the most desired plant species and varieties may cause that the content of bioactive substances in plant materials may increase, or that these plants will become more susceptible to some diseases [34][35][36][37]. Thus, the pollution and degradation of the environment will automatically reflect on the pollution of plant raw materials from which herbal medicines are obtained.…”
Section: State-of-the-art Knowledgementioning
confidence: 99%
“…Thus, the pollution and degradation of the environment will automatically reflect on the pollution of plant raw materials from which herbal medicines are obtained. The selection of the appropriate plant varieties and the cultivation of special strains of plants can play an important role in the process of obtaining the best plant materials, as is the case with 'medical marijuana' [7,34]. Growers of' 'medical marijuana' select and cultivate only those strains of Cannabis sativa that have high content of cannabimimetic substances activating cannabinoid CB1 and CB2 receptors, with a small amount of psychoactive substances [38][39][40].…”
Section: State-of-the-art Knowledgementioning
confidence: 99%